KONSEP PENDIDIKAN KELUARGA DALAM SURAT LUQMAN AYAT 12-19 - Cut Suryani (Universitas Islam Negeri Ar-Raniry, 2012)
Education is a critical need for each country, the government in general and schools in particular. Religious education is more important whereas the role of parents of children is essential during the children’s early education. Thus the first form of education present in family life. Education is nothing but emphasized the concept of Islamic education which makes the problem of servitude to God and obedience to Him become the axis of all life. It should be noted also that the child's physical education is included in the integral part and the education of the soul, mental, and personality. Duties of parents in educating children from childhood is going to introduce children the Lord that create and administer the universe, understand who is the prophet, and understand what is their religion, so that children understood the responsibility living in this world, which is to worship Allah alone by following the sunnah of His Messenger. It is obvious, that Islam tells them to carry out the education of their children, based on the view that children as beings who are growing and developing in the direction of maturity, have the basic skills which are dynamic and responsive to external influences and himself.